The Communication Style Of Sales Person - Nurul Fitria; Leonard Adrie Manafe (LPPPIPublishing, 2022)
Every human being has a different style of communication.This difference allows a person to communicate related to conveying his feelings, experiences, and needs to others in different ways.In the world of sales, the ability to Communication is very necessary and useful for a salesperson. Due to in work activities, sales will deal directly with consumers. This study aims to determine the communication style used by sales of PT. Dexa Arfindo Pratama Surabaya (DAP). The research method used is a qualitative method. Data collection techniques through interviews, direct observation in the field and documentation. The research informants were five people who were the company's sales force. The research topic is related to six communication styles, namely controlling, equalitarian, structuring, dynamic, relinquishing & withdrawal. The results of the study show that the communication style applied by DAP sales varies. The dominant communication styles used by sales are equalitarian and structuring styles.